Profile of federal purchases of insulins in Brazil: the impact of biosimilars entry (Research, Society and Development, 2022)
This study aimed to describe the acquisition by the federal government of insulins present in the Clinical Protocols and Therapeutic Guidelines (PCDTs) for Diabetes Mellitus (DM) DM1 and DM2, between the years 2015 and 2020, analyzing the amounts paid. The databases of the Integrated System for the Administration of General Services (SIASG) were consulted. The variables analyzed were supplier, purchasing agency, volume purchased, unit prices, total expenses, type of purchase and brand. Acquired Defined Daily Doses (DDD) were estimated, mean expenditures per DDD, Weighted Average Unit Prices (PMPs) and total expenditures with these drugs in the time series. A total of 2,397 insulin purchases in Brazil were analyzed, carried out between 2015 and 2020, totaling the public acquisition of about 121 million units (vials/ampoule, refills, and pens), with an expense of approximately 1.4 billion reais. Between 2015 and 2020, a reduction in average expenditure per DDD of 63% was observed for NPH insulins and 14% for regular insulins. Most of the DDDs acquired (69%) were reference medicines and 31% of DDDs were biosimilars. It is possible that the acquisitions of biosimilar insulins have contributed to the reduction of these expenses, either by increasing competition or by lower PMPs.